Human Papillomavirus Infection and Cervical Cancer Risk Modelling Among Women in Niamey, Niger Republic - Larwanou, Harouna Magagi; Lagare, Adamou; Hounkanrin, Wilfried; Issa, Moussa; Hassane, Fatimata; Eric, Adehossi; Zoubeirou, Alzouma Maiyaki (European Scientific Journal, ESJ, 2026)
Background: The impact of human papillomavirus (HPV) infection diagnosis aims to use a cervical cancer screening method in public health programs in West Africa. This study aimed to determine the prevalence of HPV infection in women in the Niger Republic. Methods: A prospective cross-sectional study was used. We randomly selected 598 women, aged 15–75 years, between January 2024 and April 2025 in four healthcare facilities providing gynecological and routine cervical cancer screening in Niamey, the capital city of the Niger Republic. We collected informed consent and assent, collected data, and trained participants to self-collect vaginal or assisted endocervical samples using FloqSwabs. HPV DNA was extracted and amplified using Genotyping Real-time PCR Kit on a Real-time PCR thermocycler (STC-48PLUS). Data were organized using Excel software, and descriptive analyses were performed using IBM SPSS Statistics 29 (IBM Corp., Armonk, NY, USA) and modelling was performed using R. Results: The overall prevalence of total HPV and HR-HPV infections in the study population was 12.20% (73/598) and 11.03% (66/598), respectively. HPV infections were confirmed among women from age group 20–29 years. The commonest HR-HPV types detected were 16 and 66, followed by HPV 35, 53, 31, 45, 52, 68, 58, 26, 51, 59, 18, 33, 39, 73, 82, and 56. The most frequently occurring Low Risk-HPV types were 6, followed by HPV 81 and 11. Multivariate logistic regression models showed no independent predictors of HPV infection. However, HPV positivity was significantly associated with an increased risk of cervical cancer. Indeed, women who tested positive for HPV had higher odds of cervical cancer diagnosis than HPV-negative women. Conclusion: The prevalence of HPV infection was assessed among women in Niamey, Niger. The study findings underscore the importance of HPV DNA genotyping and HPV vaccination are necessary for the prevention of cervical cancer in Niger and across West Africa.